Transitional cell carcinoma in dogs: a report of two cases, mother and Daughter - Martins Leal, Leonardo (2012)
The transitional cell carcinoma is usually located in the trigone region of the bladder, and shows nonspecific clinical signs of the lower urinary tract such as hematuria, strangury, pollakiuria and urinary incontinence. The urethral and ureteral obstructions occur in some cases. Etiological factors such as endogenous and iatrogenic have been listed as the cause of disease. The objective of this report is to describe the process and treatment of two cases of transitional cell carcinoma presented simultaneously in two dogs, mother and daughter, that showed hematuria and post-renal azotemia, both with tumor in the trigone of bladder. After partial cystectomy ureteroneocistostomia, the diagnosis of transitional cell carcinoma was confirmed by histopathological analysis of bladder tissue. Patients received firocoxib as adjuvant to surgery. It is concluded that the surgical procedure associated with the use of specific anti-inflammatory COX-2 provided a better quality of life in both patients.